2008
DOI: 10.1007/s12325-008-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical efficacy of flutamide and spironolactone plus ethinyloestradiol/cyproterone acetate in the treatment of hirsutism: A randomised controlled study

Abstract: Flutamide and spironolactone plus CPA/EE are effective drugs in the treatment of hirsutism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
(38 reference statements)
1
5
1
Order By: Relevance
“…In terms of hirsutism, both OCP plus spironolactone and OCP containing CPA do not seem to be strong regimens for 3 months of treatment. Although some authors could show a significant decrease in hirsutism scores from 3 months of therapy, most studies have demonstrated that OCP with and without combination of other medicines are effective after 6 months of treatment . Although the hirsutism score was significantly decreased after 3 months of OCP with CPA usage, it may have no clinical significance in the current study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In terms of hirsutism, both OCP plus spironolactone and OCP containing CPA do not seem to be strong regimens for 3 months of treatment. Although some authors could show a significant decrease in hirsutism scores from 3 months of therapy, most studies have demonstrated that OCP with and without combination of other medicines are effective after 6 months of treatment . Although the hirsutism score was significantly decreased after 3 months of OCP with CPA usage, it may have no clinical significance in the current study.…”
Section: Discussioncontrasting
confidence: 63%
“…Although some authors could show a significant decrease in hirsutism scores from 3 months of therapy, 35 most studies have demonstrated that OCP with and without combination of other medicines are effective after 6 months of treatment. [36][37][38] Although the hirsutism score was significantly decreased after 3 months of OCP with CPA usage, it may have no clinical significance in the current study. The mean initial and post-treatment mF-G scores were much lower than that of the definition of hirsutism, consistent with the fact that hirsutism is not common in Thai PCOS women.…”
Section: Discussionmentioning
confidence: 56%
“…A Cochrane review 2009 ( (Brown et al, 2009) of nine randomized controlled intervention, two trials that compared 6 months treatment of 100mg /d of spironolactone with placebo was associated with a statistically significant subjective improvement in hair growth and a decrease in Ferriman-Gallway scores (F-G), similar finding also had been revealed in other studies conducted by (Karakurt et al, 2008) and a study conducted by Poll Mara (Spritzer et al, 2000) using the same subjective clinical parameter.…”
Section: Resultssupporting
confidence: 52%
“…Spironolactone is a potassium-sparing diuretic that is used in PCOS to treat the effects of excessive androgen in women. 44,[55][56][57][58] Spironolactone inhibits the effects of aldosterone in the distal renal tubules and acts as an androgen receptor blocker interfering with steroid synthesis. Clinically, this medication has been used in patients with PCOS to effectively reduce androgen-mediated symptoms while restoring ovulation and menstrual flow.…”
Section: Pharmacological Therapymentioning
confidence: 99%